Women-Led Agri-Business Innovation Through Startups : An Opinion Survey - Pooja (AMC Indian Journal of Entrepreneurship, 2024)
Purpose : The present study focused on identifying and assessing the opinion of female respondents in the commerce and management stream toward Startup India in the educational course curriculum, analyzing and evaluating the views of respondents for agribusiness startups in the Indian context, and exploring the potential of Nari Shakti, especially the youth, to empower Viksit Bharat by 2047. Methodology : The research is analytical; hence, a descriptive research design was adopted to measure the opinion of target respondents toward agribusiness startups. For these purposes, a total of 238 responses were used, and descriptive statistics were applied. For sampling, simple random sampling was applied to collect and analyze the responses. The charts and diagrams were also used to make the study more relevant. Findings : We found that around 85–86% of respondents agreed that they intended to go for agribusiness startups when they got the opportunity to do the same. Particularly, in the views of respondents, pursuing higher education could take this opportunity hand in hand, as it was seen from their perceptions that they were highly motivated to initiate startups if they received opportunities in the future at some stage of life. Practical Implications : It was recommended that India has huge potential for growth in the field of startup business to reduce the poverty level and uplift the standards of small-scale women farmers by providing them with funding and technological assistance. In this regard, it was also suggested that students of higher education institutions (HEIs) should be provided with the opportunity to learn and develop entrepreneurial skills, especially in remote areas. Originality : Unlike prior research on agribusiness and women entrepreneurship, the current work built a new model to examine and evaluate perceptions of female students of HEIs in the commerce and management stream toward agribusiness startups. The work could have provided the basis for industry and academic collaboration to facilitate students to learn and develop entrepreneurial skills in the said field.